The little mermaid - Walt Disney Home Entertainment (Firm) (new york GENERAL AUDIIENCES, 2006)
Ariel is a fun-loving and mischievous mermaid who is enchanted with all things human. Disregarding her father's order to stay away from the world above the sea, she swims to the surface and, in a raging storm, rescues Prince Eric, the man of her dreams. Determined to be human, she strikes a bargain with the devious seawitch, Ursula, and trades her fins and beautiful voice for legs. With her best friend Flounder, and her reluctant chaperone Sebastian at her side, Ariel must win the prince's love and save her father's kingdom
Loosely based on the fairy tale by Hans Christian Andersen
Title from container
1
Keywords: Comedy films; Feature films; Mermaids $v Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs